Designing an Interactive Flip-Mind Module on Temperature and Heat Concepts to Facilitate Critical Thinking-Oriented Learning - Intan, Wahyu Noor; Susilawati, Susilawati; Kusuma, Hamdan Hadi (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
Critical thinking skills are essential for students facing the challenges of the Industrial Revolution 4.0 era. This study aimed to develop and analyze the feasibility of the Flip-Mind interactive module, evaluate the improvement of critical thinking skills, and examine students' responses to its use on temperature and heat materials. This study employed a Research and Development (R&D) method, utilizing the 4D model (Define, Design, Develop, and Disseminate), integrating case-based learning and critical thinking components through interactive HTML5-based features to enhance conceptual understanding. This research employed a pretest-posttest control group design with purposive sampling involving grade XI students from a public senior high school. The validation results indicate that the module is in the